From the pinhole camera to the shape of a lens: the camera-obscura reloaded. (23rd October 2015) - Ziegler, Max; Priemer, Burkhard
Abstract: We demonstrate how the form of a plano-convex lens and a derivation of the thin lens equation can be understood through simple physical considerations. The basic principle is the extension of the pinhole camera using additional holes. The resulting images are brought into coincidence through the deflection of light with an arrangement of prisms. This contribution describes this approach in detail and gives an illustrative experiment.